Acting early, changing lives: how prevention and early action saves money and improves wellbeing - Myfanwy McDonald
Evidence indicates worsening or unacceptably high levels of problems amongst Australia’s children and young people. These problems will not improve – and could get worse – unless we are able to effectively intervene to prevent these problems from occurring in the first place or address the problems early before they become entrenched. This report investigates the potential of early intervention to improve the outcomes of Australian children, especially those children experiencing significant levels of disadvantage, and especially for the long-term (i.e. into adolescence and adulthood). Early intervention is defined in this report as interventions that occur during the early years of an individual’s life (0-5 years of age) in order to prevent a negative outcome or to address an existing problem. The justification for early intervention (i.e. intervention during the early years) rests with the nature of human development and the way in which children develop and learn. The basic foundations for development are laid down during the early childhood years. The prenatal period also plays an important role in an individual’s longterm outcomes.&nbsp